STUDENTS' PERCEPTIONS OF THE APPLICATION OF THE SAVI MODEL IN THE TEACHING OF MAHARAH KALAM - Soumena, Iffah Maulana Putri Hanum; Wargadinata, Wildana; Hasan, Nur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to explore students’ perceptions of the implementation of the SAVI model in Maharah Kalam learning at the elementary school level. The study used a descriptive qualitative design, with a student questionnaire as the main research instrument. The questionnaire was distributed to 25 students to obtain data on their learning experiences, comfort, confidence, participation, and the SAVI components that helped them most in Arabic speaking practice. The data were analyzed descriptively by identifying patterns in students’ responses and interpreting them according to the research focus. The findings show that students gave positive responses to the implementation of the SAVI model. Most students stated that the learning process became more enjoyable, comfortable, active, and supportive of their speaking practice. The model also helped students become more confident in speaking Arabic, even when they still made mistakes. Among the SAVI components, Visual and Auditory elements were considered the most helpful. Visual media helped students remember vocabulary, while listening, imitation, and dialogue activities improved their confidence and pronunciation. Therefore, the SAVI model can be considered an appropriate learning model for Maharah Kalam because it supports active, multisensory, and student-centered learning.